Subjective poverty threshold in the Philippines - Bautista, Carlos C. ([Quezon City] School of Economics, University of the Philippines, 2010)
Subjective poverty thresholds in the Philippines are derived from a 2003 household perception survey data set. The thresholds are computed using data on the minimum income question and actual income from the survey of 1,200 households.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 155)
Keywords: Cost and standards of living -- Philippines; Poverty -- Philippines; Philippines -- Economic conditions; Philippines -- Social conditions